1992
DOI: 10.1002/arch.940210404
|View full text |Cite
|
Sign up to set email alerts
|

Role of chilling in the acquisition of cold tolerance and the capacitation to express stress proteins in diapausing pharate larvae of the gypsy moth, Lymantria dispar

Abstract: Cold hardiness in eggs (pharate first instar larvae) of the gypsy moth is not a component of the diapause program, but is acquired only after the pharate larvae have been chilled. The supercooling points of unchilled (25°C) and chilled (5°C) eggs are nearly the same (ca. -27"C), and chilling does not further elevate concentrations of glycerol, the major cryoprotectant, yet chilling at 5°C greatly increases the pharate larva's tolerance of -20°C. One conspicuous difference between the chilled and unchilled phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 31 publications
2
41
1
Order By: Relevance
“…Thus, none of the heat-shock-responsive genes are regulated as a function of diapause, suggesting that they are not involved in the expression of diapause in D. triauraria. In insects, regulation of HSPs in response to diapause has been studied only in four species, D. triauraria (Goto et al, 1998; the present study), S. crassipalpis (Yocum et al, 1998;, gypsy moth Lymantria dispar (Yocum et al, 1991;Denlinger et al, 1992) and Colorado potato beetle Leptinotarsa decemlineata (Yocum, 2001). The last two species also represent different responses from S. crassipalpis at least for the regulation of Hsp70.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, none of the heat-shock-responsive genes are regulated as a function of diapause, suggesting that they are not involved in the expression of diapause in D. triauraria. In insects, regulation of HSPs in response to diapause has been studied only in four species, D. triauraria (Goto et al, 1998; the present study), S. crassipalpis (Yocum et al, 1998;, gypsy moth Lymantria dispar (Yocum et al, 1991;Denlinger et al, 1992) and Colorado potato beetle Leptinotarsa decemlineata (Yocum, 2001). The last two species also represent different responses from S. crassipalpis at least for the regulation of Hsp70.…”
Section: Discussionmentioning
confidence: 92%
“…HSP70 is not expressed upon the initiation of diapause but only after cold temperature has been realized in Ly. dispar (Yocum et al, 1991;Denlinger et al, 1992). On the other hand, in Le.…”
Section: Discussionmentioning
confidence: 94%
“…Studies on sHsp regulation in dormancies of different organisms revealed heterogenous patterns (Bonato et al 1987;Yocum et al 1991;Denlinger et al 1992;Liang et al 1997a;Yocum et al 1998;Tammariello et al 1999;Cherkasova et al 2000;Goto and Kimura 2004;Rinehart et al 2007;Gkouvitsas et al 2008), indicating a diverse array of functions. An essential upregulation of shsp has been suggested for cold hardiness in the flesh fly Sarcophaga crassipalpis (Rinehart et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In Vrba et al (2012) the larvae were simply acclimated to constant 5°C. Assaying the cold hardiness of animals acclimated to a constant 5°C is frequently used in cold hardiness studies, as it facilitates rapid inter-species comparisons (Denlinger et al, 1992). In natural settings, however, external conditions change during winter, causing the changes in SCP values recorded here and elsewhere .…”
Section: Variation In Cold Hardiness and Cryoprotectant Contentmentioning
confidence: 99%